PERANCANGAN DESAIN KARAKTER URANG BUNIAN DALAM BUDAYA MINANGKABAU MELALUI MEDIA ART BOOK - MUHAMMAD YAZID, Hendra Afriwan, S.Sn., M.Sn., Dini Faisal, S.Ds., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Minangkabau has a unique and diverse culture, ranging from art, culture,songs, fairy tales, poems, beliefs, characterizations and visual characters. One ofthe uniqueness in Minangkabau is about beliefs that have been widely known bythe community and so the conversation from time to time until today. One of theinteresting beliefs in Minangkabau is about Urang Bunian mythology, but the lack of understanding of target audience and not optimal media in deliveringinformation about Urang Bunian visualization become the main factor of authorsto design Urang Bunian character design in Minangkabau culture through ArtBook media.Urang Bunian is made in the form of Art Book media which containsabout making character design of the information obtained. In addition to the Art Book media, the delivery of this information is also supported by several other media that help the mainstream media to introduce the subject to the target audience is posters, stickers, t-shirts, totebags, holograms, x-banners, mini xbanners. The design method used is 5w + 1h which is what, who, who, where, why (why) and how. Using the 5w + 1h theory, all the aspects summarized in the design process of character design can be born through the Art Book media.Keywords: Art Book, Urang Bunian, Mythology.